Developing a Canva-Assisted PBL e-Worksheet to Enhance Elementary Students’ Science Process Skills - Kris Agil Saraswati; Endang Widi Winarni; Abdul Muktadir; Gumono Gumono; Neza Agusdianita (AL-ISHLAH: Jurnal Pendidikan, 2026)
The effective implementation of Problem-Based Learning (PBL) in elementary classrooms remains constrained by the limited availability of digital instructional materials that systematically integrate PBL syntax, science process skills, and visual learning media aligned with the Merdeka Curriculum. This study aims to develop a PBL-based electronic student e-worksheet assisted by Canva and to examine its validity, practicality, and effectiveness in improving fourth-grade students’ science process skills. This study employed a research and development (RD) approach using the ADDIE model with a one-group pretest–posttest design. The participants consisted of 22 fourth-grade students (n = 22) at SD Negeri 05 Kepahiang, Indonesia. Data were collected through expert validation questionnaires, teacher and student response questionnaires, observations, interviews, and science process skills tests. Data analysis involved Aiken’s V for content validity and N-Gain analysis to measure the effectiveness of the intervention. The findings indicate that the developed E-worksheet demonstrates high validity across content, language, and graphical aspects, with Aiken’s V values ranging from 0.83 to 1.00. The effectiveness analysis shows a high improvement in students’ science process skills, with an average N-Gain score of 0.90. In addition, positive responses from both teachers and students confirm the practicality and usability of the E-worksheet in classroom implementation. This study concludes that the PBL-based E-worksheet assisted by Canva is a valid, practical, and effective digital instructional tool for enhancing elementary students’ science process skills.